2006
DOI: 10.1042/cs20050208
|View full text |Cite
|
Sign up to set email alerts
|

Molecular genetics of human hypertension

Abstract: EH (essential hypertension) is a major public health problem in many countries due to its high prevalence and its association with coronary heart disease, stroke, renal disease, peripheral vascular disease and other disorders. Epidemiological studies have demonstrated that EH is heritable. Owing to the fact that blood pressure is controlled by cardiac output and total peripheral resistance, many molecular pathways are believed to be involved in the disease. In this review, recent genetic studies investigating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
46
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 125 publications
0
46
0
2
Order By: Relevance
“…3 K Recently several genome-wide association studies have been performed on blood pressure and hypertension to identify the genetic factors. [4][5][6][7][8][9][10][11] What this study adds K This study provides an opportunity to identify causative non-synonymous genetic variations in a hypertension genome-wide association study. K On the basis of previous reports, newly identified genes ADC, PLD2 and BDNF seem to be relevant to hypertension, suggesting the reliability of this approach.…”
Section: Conflict Of Interestmentioning
confidence: 99%
See 1 more Smart Citation
“…3 K Recently several genome-wide association studies have been performed on blood pressure and hypertension to identify the genetic factors. [4][5][6][7][8][9][10][11] What this study adds K This study provides an opportunity to identify causative non-synonymous genetic variations in a hypertension genome-wide association study. K On the basis of previous reports, newly identified genes ADC, PLD2 and BDNF seem to be relevant to hypertension, suggesting the reliability of this approach.…”
Section: Conflict Of Interestmentioning
confidence: 99%
“…Candidate genes were selected from pathways that are implicated in blood pressure regulation-for example, the reninangiotensin system and the adrenergic system. 4 Polymorphisms in genes that control these systems have been examined for their association with hypertension, but replication studies [5][6][7] have failed to verify previously reported associations, presumably because of differences in demographics, such as age and ethnicity. 8 The first results of a genome-wide analysis of single-nucleotide polymorphism (SNP)-hypertension association were published by the Wellcome Trust Case-Control Consortium (WTCCC).…”
Section: Introductionmentioning
confidence: 99%
“…Los principales sistemas fisiológicos que se encuentran involucrados en el control de la presión arterial son el sistema renina-angiotensina-aldosterona, el endotelio vascular, la transducción de señales por vía del sistema nervioso y las proteínas del citoesqueleto, que se encargan del mantenimiento del flujo sanguíneo (presión sanguínea y volumen de fluidos extracelulares en el cuerpo), mediación de reacciones de vasodilatación-vasoconstricción y la regulación de la concentración de sales (27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44).…”
unclassified
“…Human essential hypertension accounts for 90% of the hypertensive population, is a complex multifactorial and polygenic disorder [1,2] affecting large groups with a genetic heritability ranging from 15% to 35% [3][4][5][6]. The interplay between environmental and genetic factors is a major determinant of the final phenotype in hypertension [2].…”
Section: Introductionmentioning
confidence: 99%